Ice Edge Verification -- Measuring the skill in our forecasts and disagreement in our observations ... - Niraula, Bimochan (Universität Bremen, 2023)
Sea ice is one of the most crucial components of the polar system. Alongside its effects on the climate and weather, it also impacts human lives and operations in these regions. Climate scientists, as well as other stakeholders (such as marine industries, mining operations, governmental authorities as well as local/aboriginal population), have a high interest in getting accurate observation and prediction of sea ice presence, and its effective border – the ice edge. In this context, this thesis is focused on the verification of ice presence and ice edge, across different datasets. We do this by describing a new method of generating reference forecasts of the ice edge (as benchmark for predictions at sub-seasonal to seasonal timescales), analysing initial state errors in forecasts and analysis from ECMWF, and comparing the ice presence and ice edge difference between several observational and analysis datasets. Operational systems generating sea ice forecasts at sub-seasonal timescales are mostly compared ...